2021
DOI: 10.1093/teamat/hrab018
|View full text |Cite
|
Sign up to set email alerts
|

How and why? Technology and practices used by university mathematics lecturers for emergency remote teaching during the COVID-19 pandemic

Abstract: The COVID-19 pandemic led to closures of university campuses around the world from March 2020 onwards. With little or no time for preparation, lecturers turned to emergency remote teaching to continue to educate their students. Online mathematics education poses particular challenges in terms of both the hardware and software necessary for effective teaching, due to issues with mathematical symbols and notation, among others. In this paper, we report upon an online survey of 257 university mathematics lecturer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 51 publications
(59 reference statements)
0
15
0
8
Order By: Relevance
“…There is a growing body of research (Zalat, Hamed & Bolbol, 2020;Fihloinn & Fitzmaurice, 2021;Maphalala, Khumalo & Khumalo, 2021 examining how universities and lecturers transitioned to emergency remote teaching during COVID-19 lockdowns. A study conducted in 29 countries (such as Ireland, Spain, Germany and Portugal) exploring the type of hardware and software used for emergency remote teaching for mathematics in universities found that diverse communication systems such as Skype, Microsoft Teams, Blackboard Collaborate, Zoom and pre-recorded sessions were used (Fihloinn & Fitzmaurice, 2021).…”
Section: Zulumentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing body of research (Zalat, Hamed & Bolbol, 2020;Fihloinn & Fitzmaurice, 2021;Maphalala, Khumalo & Khumalo, 2021 examining how universities and lecturers transitioned to emergency remote teaching during COVID-19 lockdowns. A study conducted in 29 countries (such as Ireland, Spain, Germany and Portugal) exploring the type of hardware and software used for emergency remote teaching for mathematics in universities found that diverse communication systems such as Skype, Microsoft Teams, Blackboard Collaborate, Zoom and pre-recorded sessions were used (Fihloinn & Fitzmaurice, 2021).…”
Section: Zulumentioning
confidence: 99%
“…There is a growing body of research (Zalat, Hamed & Bolbol, 2020;Fihloinn & Fitzmaurice, 2021;Maphalala, Khumalo & Khumalo, 2021 examining how universities and lecturers transitioned to emergency remote teaching during COVID-19 lockdowns. A study conducted in 29 countries (such as Ireland, Spain, Germany and Portugal) exploring the type of hardware and software used for emergency remote teaching for mathematics in universities found that diverse communication systems such as Skype, Microsoft Teams, Blackboard Collaborate, Zoom and pre-recorded sessions were used (Fihloinn & Fitzmaurice, 2021). Another study conducted in Egypt by Zalat, Hamed and Bolbol (2020) on the experiences of the academics during the COVID-19 pandemic reveals that synchronous (Zoom and Microsoft Teams) and asynchronous (recorded lectures, supportive videos, external links for recommended websites and electronic books) e-learning were used via a learning management system (LMS).…”
Section: Zulumentioning
confidence: 99%
“…More than 30% of the responses came from mathematicians working in Ireland. The results of the analysis of the survey data have been published in [24], [25], [26] and [27].…”
Section: The Lecturers' Perspectivementioning
confidence: 99%
“…Others made short videos or pre-recorded entire lectures. Three quarters of the respondents to Ní Fhloinn and Fitzmaurice's survey included some form of live online session in their teaching, more than 60% made recordings and over 40% had both [26]. Lecturers who chose to have live sessions said that they did so in order to facilitate students' questions and to try to keep the format as close to that of their regular classes as possible.…”
Section: The Lecturers' Perspectivementioning
confidence: 99%
See 1 more Smart Citation